Behavior of beryllium in the weathering environment and its delivery to the ocean. (15th November 2019) - Suhrhoff, Tim Jesper; Rickli, Jörg; Crocket, Kirsty; Bura-Nakic, Elvira; Vance, Derek
Abstract: Chemical weathering of silicate rock is one of the major long-term sinks of atmospheric CO2 . While several radiogenic isotope systems (e.g. Nd, Pb, Os) in the authigenic component of marine sediments show temporal patterns that could be interpreted in terms of fluctuations in chemical weathering rate over glacial cycles, recent work using beryllium isotopes suggests little such variation. However, our knowledge of the sources of 9 Be to the oceans is incomplete. Here, we address some of the gaps in knowledge with new data on Be in Croatian and Scottish rivers and estuaries, as well as with mixing experiments between Amazon tributaries and ocean water. The new data, combined with data from the literature, confirm that riverine Be is only marginally affected by carbonate weathering, which only accounts for 0.4–1.5% of dissolved riverine Be fluxes. The behavior of Be in estuaries is highly variable, with some estuaries showing removal and others addition. Based on the available data, about 55% of dissolved riverine Be is removed in estuaries, with complexation by both organic vs. inorganic ligands appearing to exert a strong control on the specific behavior in a given estuary. Beryllium complexation with organic material facilitates transport across estuaries, whereas the presence of inorganic complexants results in loss. Presence of both ligand types may lead to stronger non-conservative behavior than the presence of only one. Combining different approaches for estimating the dissolved riverine Be flux and estuarine removal, we calculate that 13–30% (4–48% error range) of the marine 9 Be input is derived from riverine dissolved loads, and 70–87% (53–96% error range) from other sources like desorption from particulate matter and release from shelf sediments. It seems likely that this 13–30% of the marine Be input would respond quickly to changes in continental weathering rates, instantaneously impacting marine Be isotopes. However, the exact response of marine Be isotopes to changes in continental weathering rates also depends on the timescale of Be release from the riverine particulate pool stored in sediments on continental margins.